PENGADMINISTRASI PENDIDIKAN DALAM MENINGKATKAN KUALITAS PENGELOLAAN LEMBAGA PENDIDIKAN - Muhammad Nur Kurniawan; Syahrani Syahrani (CV. ADIBA AISHA AMIRA, 2021)
Educational administration for teachers is very important to support the process of teaching and learning activities and also not only for the teaching and learning process but is also useful for the quality or quality of education itself. Where educational administration implies the process to achieve educational goals. The process starts from planning, organizing, coordinating, directing, monitoring and evaluating. Planning includes activities to determine what you want to achieve, how to achieve it, how long, how many people are needed, and how much it will cost. This planning is made before an action is carried out.